SOEP scales manual - David Richter; Maria Metzing; Michael Weinhardt; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This manual briefly describes the theoretical background and development of all of the scales used in the Socio-Economic Panel (SOEP) study. It also provides the relevant citations as well as the items belonging to the scales and the answer format, including the verbal anchors. The unique value of this manual lies in the presentation of each scale in the form of easy-tounderstand tables listing variable names of the items in the scale in a wave-specific dataset (labels). This allows the individual items to be found and aggregated quickly. In addition, the tables in this manual include mean values (M), standard deviations (SD), corrected item-total correlations (CITC), and information as to whether the item has to be recoded before aggregation (R). The number of valid cases in the particular survey years and the internal consistency of the scale (Cronbach's Alpha) are also reported as a measure of each scale's reliability.
Keywords: 330